Leadership Role In Startup Success - Viyen Mawar Sandagang; Wirna Buana Aras Abadi; Prayoga Kupande (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
A prospective and potentially profitable firm is a start-up that can expand. This study seeks to investigate the elements that impact the success of start-up firms by looking into young entrepreneurs who created digital start-ups in Gorontalo. A purposive sample strategy was used to pick eleven startup entrepreneurs from Gorontalo province. The Structural Equation Model—Partial Least Squares (SEM-PLS) was used in conjunction with SPSS and WARP PLS 8.0 to conduct analysis. This study employs human, social, and financial capital as independent factors, with company performance and innovation serving as mediating variables. The study's findings indicate that human and social capital have a substantial impact on corporate performance.